Pengawasan Kualitas Beton Pada Proyek Dinding Penahan Tanah Kejaksaan Tinggi Sumatera Selatan - Sonia; Ely Mulyati (Yayasan Literasi Sains Indonesia, 2025)
This study aims to describe the process of monitoring the quality of concrete in the retaining wall construction project at the South Sumatra High Prosecutor's Office. The concrete used is a type of ready mix quality K-175, with supervision carried out through the stages of slump test, sample collection and curing, and concrete compressive strength test. This research uses a qualitative descriptive method with a case study approach. The results showed that the concrete slump value was within the specification range (10-12 cm), while the concrete compressive strength test results at the age of 7 days reached an average of 181.469 kgf/cm² and at the age of 14 days amounted to 188.397 kgf/cm². These values indicate that the concrete has met the technical strength requirements for non-structural structures. Some field constraints such as high rainfall and delays in concrete delivery can be overcome by rescheduling, the use of work area protection, and good logistical coordination. Overall, the concrete quality in this project was in accordance with the set standards.